The Linux networking architecture: (Pearson / Prentice Hall, 2005)
Written by experts, this unique Linux networking tutorial/reference provides a practical overview and understanding of the implementation of networking protocols in the Linux kernel. The organization of the book follows the TCP/IP layering model, beginning with the kernel's network device drivers, continuing with link-layer protocols such as PPP, and finally giving a description of all core protocols of the TCP/IP protocol family.